Estimation of Slip Rate and the Opak Fault Geometry Based on GNSS Measurement - Adam, Jiyon Ataa Nurmufti; Widjajanti, Nurrohmat; Pratama, Cecep (2019)
GNSS observations are usually used in periodic deformation monitoring. The Opak fault, which was in the Special Region of Yogyakarta, became a concern after the 2006 earthquake. The horizontal velocity values of each observation station are needed to estimate the slip rate and locking depth values of the Opak fault. The magnitude of the velocity vector is computed by the linear least square method, then translated into the Sunda Block reference frame. The creep of fault assumption is used in analyzing the potential for the earthquake in the Opak fault region. The velocity is done by reducing the Sunda Block using the Euler pole method, and it produces a velocity vector value on the east component is -6.08 to 5.25 mm/year while the north component is -3.38 to 5.74 mm/year. Meanwhile, in the northern segment of the Opak fault, the estimated slip rate is around 3.5 to 10.5 mm/year, with the locking depth obtained of 1.1 to 8 km, while in the southern segment of the Opak fault, the estimated slip rate is 4 to 5.5 mm/year, with a locking depth obtained of 0.6 to 1.2 km. The creep of the fault effect is predominantly in the southern segment of the Opak fault. This case indicates that the potential for earthquake hazards is smaller in the south segment than in the north segment.